Proyecto de acompañamiento psicológico para facilitar los procesos de simbolización en los niños y niñas que acuden al reforzamiento escolar del centro de acogida Mi Caleta en el periodo abril-julio 2015. - Román Carrión, Valeria Stephany (2016)
Temporary hosting center "Mi Caleta" offers the service of tutoring to children about the precarious economic situation of their families working as street vendors in the streets of Quito, it aims to equip all educational resources to improve academic performance and prevent school dropouts, those charged with reinforcement is an educator and a foreign volunteer and found that the most common problem of children to do homework are aggressive and very demanding, as well as impulsivity and isolation behavior. This set of behaviors respond to a failure in the process of symbolization, which worked on the psychological support intervention with ten of them using fun techniques, which helped users to express their thoughts and emotions achieving transformation of some of the aforementioned behaviors, improving their quality of life